2016
DOI: 10.1118/1.4960629
|View full text |Cite
|
Sign up to set email alerts
|

Practical reconstruction protocol for quantitative 90Y bremsstrahlung SPECT/CT

Abstract: Purpose: To develop a practical background compensation (BC) technique to improve quantitative 90 Y-bremsstrahlung single-photon emission computed tomography (SPECT)/computed tomography (CT) using a commercially available imaging system. Methods: All images were acquired using medium-energy collimation in six energy windows (EWs), ranging from 70 to 410 keV. The EWs were determined based on the signal-to-background ratio in planar images of an acrylic phantom of different thicknesses (2-16 cm) positioned below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 38 publications
1
74
0
1
Order By: Relevance
“…Investigators have reported on the positive role of 90 Y planar and 90 Y bremsstrahlung SPECT/CT in disease management after 90 Y‐SIRT . Furthermore, 90 Y SPECT/CT also facilitates dosimetry at the voxel level that allows for investigations into the volume distribution of absorbed doses in tumors and normal liver tissue . A number of approaches have been described in the literature for generation and quantitation of 90 Y bremsstrahlung SPECT/CT, as described in a recent review article .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators have reported on the positive role of 90 Y planar and 90 Y bremsstrahlung SPECT/CT in disease management after 90 Y‐SIRT . Furthermore, 90 Y SPECT/CT also facilitates dosimetry at the voxel level that allows for investigations into the volume distribution of absorbed doses in tumors and normal liver tissue . A number of approaches have been described in the literature for generation and quantitation of 90 Y bremsstrahlung SPECT/CT, as described in a recent review article .…”
Section: Introductionmentioning
confidence: 99%
“…A number of approaches have been described in the literature for generation and quantitation of 90 Y bremsstrahlung SPECT/CT, as described in a recent review article . Some of the approaches for 90 Y SPECT quantitation include Monte Carlo‐based modeling of SPECT corrections and reconstructions to multiple energy window–based scatter compensations …”
Section: Introductionmentioning
confidence: 99%
“…Since β‐radiation emitted by 90 Y interacts with body tissues resulting in Bremsstrahlung radiation, SPECT/CT has traditionally been regarded as the gold‐standard modality to image the biodistribution of this radionuclide. However, the low photon yield and continuous nature of the Bremsstrahlung x‐ray spectrum make SPECT imaging involving 90 Y technically challenging 17. On the other hand, the 90 Y decay to the 0 + excited state and then ground state of 90 Zr may result in emission of a positron‐electron pair.…”
Section: Discussionmentioning
confidence: 99%
“…For therapy, 90 Y glass microspheres (TheraSphere, BTG Inc., Ottawa, Canada) were administered with an activity calculated according to the manufacturer's specifications 3. Within 90 min after the administration of the 90 Y, a bremsstrahlung SPECT/CT was acquired using a Siemens Symbia T6 (Siemens Medical Solutions Inc., Malvern, PA) with an energy window of 90–125 keV based on a highly optimized acquisition and reconstruction protocol published by Siman et al 17. The SPECT projection images were acquired with a matrix size of 128 × 128, 4.8 mm pixel size, 28 s/view for 128 views over 360°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation